2014
DOI: 10.1017/s0954579414000753
|View full text |Cite
|
Sign up to set email alerts
|

Temperament as a moderator of the effects of parenting on children's behavior

Abstract: This study examined the role of child temperament as moderator of the effect of parenting style on children's externalizing and internalizing behaviors. A series of structural equation models were fit to a representative sample of 2,631 Canadian children from the National Longitudinal Survey of Children and Youth. In addition to testing for the presence of Temperament × Parenting interactions, these models also examined the direct and indirect effects of a number of additional contextual factors such as neighb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 126 publications
(136 reference statements)
2
25
0
4
Order By: Relevance
“…3 The news is not entirely grim. In a study of 2,631 children from the Canadian National Longitudinal Survey of Children and Youth, Gallitto (2014) reported that children with difficult temperaments who were exposed to more positive parenting had reduced problem behaviors. 4 Even studies that purport to find questionable field reliability of psychopathy measures nevertheless show significant agreement in assessments of psychopathic offenders.…”
Section: Potential Integration and Discussionmentioning
confidence: 99%
“…3 The news is not entirely grim. In a study of 2,631 children from the Canadian National Longitudinal Survey of Children and Youth, Gallitto (2014) reported that children with difficult temperaments who were exposed to more positive parenting had reduced problem behaviors. 4 Even studies that purport to find questionable field reliability of psychopathy measures nevertheless show significant agreement in assessments of psychopathic offenders.…”
Section: Potential Integration and Discussionmentioning
confidence: 99%
“…One cannot deny the role of child temperament as a mediator in the effect of parenting [24]. Children with more difficult/unadaptable temperaments respond more negatively to a lack of positive parenting and, then, present worsened externalizing and internalizing behavioral problems, compared with those without such temperamental characteristics [24].…”
Section: Discussionmentioning
confidence: 99%
“…Children with more difficult/unadaptable temperaments respond more negatively to a lack of positive parenting and, then, present worsened externalizing and internalizing behavioral problems, compared with those without such temperamental characteristics [24]. Future studies should investigate the association among parental educational social skills (or parenting styles), child behavior during procedural sedation and child temperament.…”
Section: Discussionmentioning
confidence: 99%
“…This scale included 33 descriptions of difficult behaviors; examples are “Disobedient at home,” “Gets in many fights,” “Stubborn, sullen, or irritable,” and “Uses alcohol or drugs.” Response options ranged from 0 ( Not true [as far as I know] ) to 2 ( Very true or often true ). The CBCL has demonstrated strong associations with other measures of child externalizing behaviors as well as positive and negative parenting behaviors (e.g., Gallitto 2015; Pearl et al 2014). Cronbach’s alpha for this scale was .81.…”
Section: Methodsmentioning
confidence: 99%